Penurunan Kualitas dan Kuantitas Spermatozoa Mencit (Mus musculus L.) Setelah Pemberian Ekstrak Rimpang Rumput Teki ( Cyperus rotundus L.) - Indri indriyani; Hendri Busman; Sutyarso Sutyarso (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
The lack of participation of men in family planning programs is due to the limited choice of male contraceptive. Traditional medicinal plants are one of ideal alternative types of male contraception. This study aimed to study the effect of Cyperus rotundus L. rhizome on the quality and quantity of spermatozoa in male mice (Mus musculus L.). Twenty male mice were divided into four treatment groups, namely control group (C0), the dose of teki grass rhizome extract 4.5 mg/40 g BW (C1), the dose of teki grass rhizome extract 45 mg/40 g BW (C2), and the dose of teki grass rhizome extract 135 mg/40 g BW (C3) for 35 days. Parameters measured were the motility, viability, morphology, and concentration of spermatozoa. The data were analyzed for diversity and then further tested using the LSD test with a 5% significance level. The results of the analysis showed that giving teki grass rhizome extract had a significant effect on the motility, viability, morphology, and concentration of spermatozoa. It can be concluded that teki grass rhizome can be used as an alternative male contraception because it can reduce motility, viability, morphology, and spermatozoa concentration.